Leadership in a crisis: doing things differently, doing different things. (2nd November 2020) - Paixão, Graça; Mills, Chloe; McKimm, Judy; Hassanien, Mohammed A; Al-Hayani, Abdulmonem A
Abstract : This article summarises the findings from a review of publications related to healthcare leadership that were published during the first wave of the COVID-19 crisis in 2020. The review discusses a range of strategies for leaders to adopt in challenging situations and identifies three aspects of leadership which are considered essential when leading teams during a crisis: 1) communication, 2) decision making and 3) mental health and wellbeing. This article identifies key principles for each of these three aspects and provides practical tips for how leaders can use the lessons learned from the pandemic in their own contexts.